Immunoglobulin J chain gene from the mouse. - Matsuuchi, L (1986)
During a primary immune response, murine B lymphocytes are induced to express the gene for the immunoglobulin J chain. As a first step in determining the mechanism of induction, genomic DNA clones encoding the murine J chain were obtained from cell lines representative of B lymphocytes before and after J chain expression. Analysis of the coding regions showed that the J chain gene has a different structure from the other immunoglobulin genes. It consists of four exons organized in a simple 7.3-kilobase transcription unit that does not require DNA rearrangement or alternative processing for expression. These structural properties indicate that transcription of the J chain gene is initiated by changes in chromatin conformation, probably involving a J chain-specific DNA-binding factor. Analysis of the 5' flanking sequences of the J chain gene, on the other hand, showed that the promoter region contains two conserved elements that have been implicated in the lymphocyte-specific expression of the light chain genes. The sharing of these elements suggests that, once the J chain gene is activated, its transcription is regulated by mechanisms similar to those controlling the light chain genes.